(untitled) (Applied Biological Research, 2018)
The experiment was carried out with the aim to study floral biology of jackfruit using 10 jackfruit genotypes at AICRP on Fruits, BCKV, Mondouri, West Bengal (India). Floral buds since initiation were continuously observed for a set of parameters.Bud development in jackfruit took 28-46 days while successive spike openings took 8–36 days and spikes opening to spathe shedding 8-16 days. In male spike opening to anthesis ranged from 16 to 32 days and anther sacs availability for 3-7 days. In female spikes, stigmas were available from 12-34 days and receptive from 5th to 34th days after emergence. Female spike length ranged from 4.65 to 9.80 cm and diameter from 3.18 to 5.90 cm. Sex ratio was highest in December. Male spike length was 3.8-10.9 cm and diameter 1.60-3.78 cm. Number of individual flowers spike-1 was 3565- 9831 for female and 2736-1294 for male. The study revealed that genotypes 10/9, 11/6, 11/9 and 11/10 can be used for future crop improvement based on reproductive traits of male and female parents that ultimately indicates the quality and yield potential of those individuals.